The Role And Importance Of Combat Training Exercises Simulating Real Combat Situations In Enhancing The Fighting Spirit Of Military Personnel (Academicia Review-A Multidisciplinary Online Journal, 2026)
The present study examines the critical role of combat training exercises simulating real-life battlefield conditions in strengthening the fighting spirit, psychological readiness, and overall combat effectiveness of military servicemen. Drawing on contemporary military pedagogy and empirical research, the article analyzes how realistic training environments replicate the physical, psychological, and tactical demands of actual combat, thereby reducing fear, increasing confidence, and developing cohesive unit performance. The study argues that exercises designed to approximate genuine combat stress - including live-fire drills, night operations, urban warfare simulations, and stress inoculation training - produce measurable improvements in individual soldier resilience and collective military readiness. The article also reviews legislative and doctrinal foundations governing military training in Uzbekistan and highlights international best practices. The findings suggest that investment in high-fidelity training scenarios directly correlates with superior battlefield outcomes, lower casualty rates, and a stronger will to fight among armed forces personnel.
Keywords: combat training; fighting spirit; military readiness